Pengaruh Ukuran Kap, Ukuran Perusahaan, Solvabilitas, Struktur Kepemilikan Terhadap Audit Delay (Studi Kasus Pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2010 - 2014) - Priyambodo, Danang; , Drs. Atwal Arifin, M.Si., Akt (2016)
This research is a study that tested the effect of Firm Size , Company Size , Solvency , Ownership Structure Audit Against Delay in companies listed on the Indonesia Stock Exchange. The sample in this study using purposive sampling and obtained a sample of 120 companies listed on the Indonesia Stock Exchange in 2010-2014. Methods of data analysis using logistic regression. The results of this study indicate the size of the company and ownership structure affect the audit delay while the size of the firm and does not affect the solvency of the audit delay